VDJ Gene Usage in IgM Repertoires of Rhesus and Cynomolgus Macaques - Chernyshev, Mark; Kaduk, Mateusz; Corcoran, Martin; Karlsson Hedestam, Gunilla B. (Frontiers in Immunology, 2022)
Macaques are frequently used to evaluate candidate vaccines and to study infection-induced antibody responses, requiring an improved understanding of their naïve immunoglobulin (IG) repertoires. Baseline gene usage frequencies contextualize studies of antigen-specific immune responses, providing information about how easily one may stimulate a response with a particular VDJ recombination. Studies of human IgM repertoires have shown that IG VDJ gene frequencies vary several orders of magnitude between the most and least utilized genes in a manner that is consistent across many individuals but to date similar analyses are lacking for macaque IgM repertoires. Here, we quantified VDJ gene usage levels in unmutated IgM repertoires of 45 macaques, belonging to two species and four commonly used subgroups: Indian and Chinese origin rhesus macaques and Indonesian and Mauritian origin cynomolgus macaques. We show that VDJ gene frequencies differed greatly between the most and least used genes, with similar overall patterns observed in macaque subgroups and individuals. However, there were also clear differences affecting the use of specific V, D and J genes. Furthermore, in contrast to humans, macaques of both species utilized IGHV4 family genes to a much higher extent and showed evidence of evolutionary expansion of genes of this family. Finally, we used the results to inform the analysis of a broadly neutralizing HIV-1 antibody elicited in SHIV-infected rhesus macaques, RHA1.V2.01, which binds the apex of the Env trimer in a manner that mimics the binding mode of PGT145. We discuss the likelihood that similar antibodies could be elicited in different macaque subgroups.